Land system changes of terrestrial tipping elements on Earth under global climate pledges: 2000–2100 - Jiaying Lv; Yifan Gao; Changqing Song; Li Chen; Sijing Ye; Peichao Gao (Scientific Data)
Abstract Tipping elements on Earth are components that undergo rapid and irreversible changes when climate change reaches a tipping point. They are highly sensitive to climate variations and serve as early warning signs of global change. Human activities, including global climate pledges, significantly influence the climate and the state of tipping elements. Land changes serve as the external and intuitive response of tipping elements to climate change, making it essential to identify shifts in the land system. We produced a 1-km land system dataset for terrestrial tipping elements on Earth for the years 2000, 2010, 2020, and 2100 under global climate pledges by integrating the GCAM with a modified version of CLUMondo. Our dataset includes 30 thematic categories, combining three density types and ten land cover types. The dataset illustrates potential land system changes under global climate pledges, contrasting with common SSP and RCP scenarios. Our simulations demonstrate high accuracy, offering valuable insights into tipping elements and the assessment of the impacts of global climate pledges on Earth.